Wireless Sensor Networks Routing Methodology To Increase Life Span Of An Operative Environment - pradeep S, harini R, nivetha S, poomathy P (International Journal of Modern Agriculture, 2021)
The majority of sensor networks employ dynamic steering conventions, which enable the guiding geography to evolve in response to natural changes.As packages and environmental consequences grow, routing behaviours can become very complex. We have proposed the EAR-DCP (Energy Aware Routing Dynamic Clustering Protocol) scheme, which is implemented at the WSN to increase load balancing and network longevity. The proposed based on the Maximum capacity path based multi hop routing by implementing theprotocol considers both energy efficiency and transmission distance, and sink nodes are used to reduce the cluster heads’ excessive power consumption. As a result of the proposed system, better distributed sensor networks and a well-balanced clustering system are achieved, extending the lifespan of the network.For the implementation, we need to calculate the initial energy of nodes, residual energy and optimum energy path. Parameters like efficient path and CH hierarchy will be ensured in order to improve the networks lifespan and its performance.